E-education in pathology including certification of e-institutions - Borkenfeld Stephan; Ogilvie Robert; Kayser Klaus; Kayser Gian (BMC, 2011)
Abstract E-education or electronically transferred continuous education in pathology is one major application of virtual microscopy. The basic conditions and properties of acoustic and visual information transfer, of teaching and learning processes, as well as of knowledge and competence, influence its implementation to a high degree. Educational programs and structures can be judged by access to the basic conditions, by description of the teaching resources, methods, and its program, as well as by identification of competences, and development of an appropriate evaluation system. Classic teaching and learning methods present a constant, usually non-reversible information flow. They are subject to personal circumstances of both teacher and student. The methods of information presentation need to be distinguished between static and dynamic, between acoustic and visual ones. Electronic tools in education include local manually assisted tools (language assistants, computer-assisted design, etc.), local passive tools (slides, movies, sounds, music), open access tools (internet), and specific tools such as Webinars. From the medical point of view information content can be divided into constant (gross and microscopic anatomy) and variable (disease related) items. Most open access available medical courses teach constant information such as anatomy or physiology. Mandatory teaching resources are image archives with user-controlled navigation and labelling, student-oriented user manuals, discussion forums, and expert consultation. A classic undergraduate electronic educational system is WebMic which presents with histology lectures. An example designed for postgraduate teaching is the digital lung pathology system. It includes a description of diagnostic and therapeutic features of 60 rare and common lung diseases, partly in multimedia presentation. Combining multimedia features with the organization structures of a virtual pathology institution will result in a virtual pathology education institution (VPEI), which can develop to a partly automated distant learning faculty in medicine.